"Composición química del ensilaje del pasto king grasas (Penniselum hybridum) con diferentes edades de corte e inclusión de rechazo de la pulpa de piña (Ananas comosus)" - Quijije Zambrano, María Belén (2020)
The research was carried out at the “La María” Campus, belonging to the Quevedo State Technical University, in the rumiology laboratory. The general objective of the study was the analysis of the chemical composition of the King Grass silage (Pennisetum hybridum) with different cutting ages (30, 40, 50 days) plus the inclusion of the rejection of the Pineapple (Ananas comosus) pulp. For the research, a completely randomized design (DCA) with eight treatments and five repetitions was applied. The grass had a particle cut size between 0,5 and 1 cm. The following chemical variables were studied: dry matter (MS), inorganic matter content (MI), crude protein content (PB), energy content, neutral detergent fiber content (FDN) and acid detergent fiber content (FDA), resulting in the highest dry matter content recorded in T2 (100% pineapple residue), in inorganic matter the highest value was expressed in T7 (fresh king grass cut after 40 days). The highest value in neutral detergent fiber and acid detergent fiber was obtained in T1 (King grass silage at 40 days). The highest average crude protein was recorded in T6 (fresh king grass cut at 30 days) , followed by T5 (silage of king grass 50 days and inclusion of rejection of pineapple pulp). The highest energy content was determined in T1 (King grass silage at 40 days). Keywords: dry matter, ADF, NDF, crude protein